The Role of Educational Interventions in Mitigating Risk Factors for Stunting in Adolescent Girls - Yuniarti; Zakiah; Hapisah (Postgraduate, University of Mataram, 2025)
Stunting is a nutritional problem that affects children's growth and development. Various risk factors, including education, diet, and maternal health, contribute to stunting prevention. This study aims to analyze the factors influencing stunting, focusing on adolescent girls as a vulnerable group. This study used a quantitative analytical approach with a cross-sectional design, conducted in Tabukan District, Barito Kuala Regency, from March to September 2025. The sample consisted of 77 adolescent girls aged 10 to 14 years old, selected based on inclusion criteria. Data were collected through a questionnaire covering knowledge and stunting prevention behaviors, hemoglobin levels, Body Mass Index (BMI), and Mid-Upper Arm Circumference (MUAC). Logistic regression analysis was used to identify significant relationships between variables. The results showed Significant relationships were found between knowledge and parenting patterns (p=0.000), physical activity (p=0.031), and diet (p=0.017). Hemoglobin levels were significantly associated with adherence to iron supplementation (IBT) consumption (p=0.000). In Conclusion, Adolescents' lack of knowledge about stunting prevention impacts their parenting, diet, and health. The poor distribution of parenting patterns and low adherence to iron supplementation indicate the need for nutrition education-based interventions.